Exploring the Fictional World in The Rime of the Ancient Mariner: A Critical Stylistic Study (Journal of the College of Languages (JCL), 2024)
Critical stylistics is an interesting area that explores ideologies and social concepts, specifically in literary genres. Although critical stylistic studies are increasing, limited studies have explored social concepts in Romantic poetry. Hence, this qualitative study aimed at exploring the construction of the fictional world in The Rime of the Ancient Mariner by Samuel Taylor Coleridge employing Functional Grammar. The poem was analyzed to highlight the linguistic elements that contribute to the construction of the fictional world by Coleridge. Nominal and verbal groups, word order, and deictic expressions were analysed within the framework of Critical Stylistics. The findings revealed that nouns and their descriptions are sometimes incompatible with the fictional world of Coleridge. Verbs are used to express the speaker's full control over the hearer and other characters in the poem. These linguistic phenomena were employed with varied frequencies. The findings of the study, firstly, extended the existing knowledge of the critical stylistic description of poetry, and secondly illustrated how the combination of linguistic elements could present new meanings.